Cytotoxic T-lymphocyte epitopes for HLA-B53 and other HLA types in the malaria vaccine candidate liver-stage antigen 3. - Aidoo, M; Lalvani, A; Gilbert, S; Hu, J; Daubersies, P; Hurt, N; Whittle, H; Druihle, P; Hill, A (2000)
The development of an effective preerythrocytic vaccine against Plasmodium falciparum malaria is likely to require inclusion of components from several preerythrocytic antigens. The association of HLA-B53 with resistance to severe malaria in West Africa provided evidence that HLA class I-restricted CD8(+) T-cell responses play a role in protective immunity in African children, supporting data from rodent models of malaria. Previously, a single epitope from liver-stage-specific antigen 1 (LSA-1) has been shown to be recognized by HLA-B53-specific cytotoxic T lymphocytes (CTL), but HLA-B53 epitopes were not found in four other antigens. In this study we measured CTL responses to peptides from the recently sequenced antigen liver-stage antigen 3 (LSA-3) and identified in it a new epitope restricted by HLA-B53. Several CTL epitopes restricted by other class I types were also identified within LSA-3 in studies in The Gambia and Tanzania. CTL were also identified to an additional P. falciparum antigen, exported protein 1 (Exp-1), the homologue of which is a protective antigen in a rodent model of malaria. These findings emphasize the diversity of P. falciparum antigens recognized by CD8(+) T cells in humans and support the inclusion of components from several antigens in new CTL-inducing vaccines against malaria.